Pengenalan Augmented Reality pada Pendidikan Bagi Siswa dan Guru SMK Negeri 1 Magelang - Renna Yanwastika Ariyana; Uning Lestari; Erna Kumalasari Nurnawati (Jurnal Pengabdian Masyarakat (abdira), 2022)
Utilizing Augmented Reality (AR) technology which is currently developing in presenting the material to be taught to students is one method that can be used in innovating learning materials. SMK Negeri 1 Magelang as one of the schools that wants to present more interesting learning materials certainly requires technology references to develop effective, creative and innovative learning media. Utilizing AR technology by providing knowledge on how to package learning using AR technology is certainly very beneficial for teachers and students of SMK Negeri 1 Magelang. Conducting community service by providing AR technology introduction materials, especially for the world of education, will certainly be very useful. The method used in the implementation is by online seminars. The results obtained from this activity are a positive impact for students and teachers, because they have additional knowledge related to AR technology that can be used in the teaching and learning process. Students and teachers can also find out tools and device specifications in developing AR.